Identification of Sex from Maxillary Sinus in Western Maharashtra Population - Umang P Patel 1 , Makardar U K2 , Karkhyle Md. Layeeqeu3 , Kailash Balkund4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: As Maxillary Sinus are pneumatic bones delicate in cadavers, Morphological study hasanatomical anthropological and medico legal important. Hence Morpho metric parameters of MXS in CTscan of both sexes were studied.Methods: 23 male 23 female adult aged between 20-50 year healthy people were studied with CT images tomeasure medio-lateral, superoinferior and antero posterior dimensions and volumes of MXS in both sexesand results were analysed statistically.Results: In ML Right mean values Males was 29-30 (SD±3.17), female 27.12 (SD±5.16 t test was 1.72and p<0.001. SIR Right – Mean value of male was 40.02 (SD±3.66), female 35.11 (SD±4.40) t test 4.11and p<0.001. AP (right side) Mean value of male was 44.23 (SD±3.21), female 38.03 (SD±2.30) t test 7.53p<0.00. MLC (left side) mean value of male was 29.04 (SD±2.30), female 25.06 (SD±4.20) t test 3.98p<0.004. SIL left side mean value of male 38.41 (SD±4.12), female 35.07 (SD±3.60) t test 2.92 p<0.005.APL (left side) mean value of male 42.36 (SD±2.60), female 39.05 (SD±2.45) t test value 4.44 p<0.001.The volumes study of MXS had VR – mean value of male 18.25 (SD±2.53), female 13.30 (SD±3.14) t test5.88 p<0.041. In VL study mean value of male was 17.09 (SD±2.75), female was 12.44 (SD±3.42) p<0.001.Conclusion: This pragmatic study of sexual dimorphism will be quite useful to medico-legal expert,anthropologist and anatomist